A Holistic Look at Minimizing Adverse Environmental Impact Under Section 316(b) of the Clean Water Act - John A. Veil; Markus G. Puder; Debra J. Littleton; Nancy Johnson (The Scientific World Journal)
Section 316(b) of the Clean Water Act (CWA) requires that “the location, design, construction, and capacity of cooling water intake structures reflect the best technology available for minimizing adverse environmental impact.” As the U.S. Environmental Protection Agency (EPA) develops new regulations to implement Section 316(b), much of the debate has centered on adverse impingement and entrainment impacts of cooling-water intake structures. Depending on the specific location and intake layout, once-through cooling systems withdrawing many millions of gallons of water per day can, to a varying degree, harm fish and other aquatic organisms in the water bodies from which the cooling water is withdrawn. Therefore, opponents of once-through cooling systems have encouraged the EPA to require wet or dry cooling tower systems as the best technology available (BTA), without considering site-specific conditions.